Ubiquitous waterborne pathogens - Magana-Arachchi, D.N. (Waterborne Pathogens, 2020)
Water is one of the most important substances on earth and without it life cannot exist. However, poor water quality in many parts of the world has increased the number of water-related diseases, making it the leading cause of disease and death globally for both young and old. Waterborne pathogens cause diseases in humans through two major exposure pathways: drinking water and recreational waters. This chapter on waterborne pathogens will be starting with an introduction, followed by descriptions on classical waterborne pathogens; bacteria, viruses, protozoans, and helminths placing emphasis on the World Health Organization guidelines. Further to conventional waterborne pathogens, fresh organisms and new strains from already known pathogens are being identified and that present important additional challenges to both the water and public health sectors. Hence later part of the chapter focuses on the potential waterborne pathogens and will conclude with a summary of the content.